Classic questions & contemporary film : an introduction to philosophy / Dean A Kowalski - Kowalski, Dean A.
Featuring significant revisions and updates, Classic Questions and Contemporary Film: An Introduction to Philosophy, 2nd Edition uses popular movies as a highly accessible framework for introducing key philosophical concepts Explores 28 films with 18 new to this edition, including€Eternal Sunshine of the Spotless Mind, Hotel Rwanda, V for Vendetta, €and€Memento Discusses numerous philosophical issues not covered in the first edition, including a new chapter€ covering issues of personal identity, the meaningfulness of life and death, and existentialism Offers a rich pedagogical framework comprised of key classic readings, chapter learning outcomes, jargon-free argument analysis, critical thinking and trivia questions, a glossary of terms, and textboxes with notes on the movies discussed Revised to be even more accessible to beginning philosophers.